2016
DOI: 10.3168/jds.2015-10705
|View full text |Cite
|
Sign up to set email alerts
|

Association analysis for feet and legs disorders with whole-genome sequence variants in 3 dairy cattle breeds

Abstract: Identification of genetic variants associated with feet and legs disorders (FLD) will aid in the genetic improvement of these traits by providing knowledge on genes that influence trait variations. In Denmark, FLD in cattle has been recorded since the 1990s. In this report, we used deregressed breeding values as response variables for a genome-wide association study. Bulls (5,334 Danish Holstein, 4,237 Nordic Red Dairy Cattle, and 1,180 Danish Jersey) with deregressed estimated breeding values were genotyped w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 34 publications
5
35
1
Order By: Relevance
“…Although the number of published studies related to GWAS for hoof and leg disorders is very limited, their common feature is the lack of overlap in significant results both, between and even within the studies. Similarly, to our study, Wu et al [9] applied the same GWAS model to feet and leg disorders in three breeds and depending on breed identified different significant regions between Danish Red and Danish Holstein, while no significance was observed in Jersey. In addition, earlier van der Spek et al [10] found a very low overlap in significance while analysing a cow data set and a bull data set ascertained from the same population of Holstein-Friesian cattle, with only three SNPs in bulls overlapped with 94 SNPs significant for claw disorders in cows.…”
Section: Discussionsupporting
confidence: 83%
“…Although the number of published studies related to GWAS for hoof and leg disorders is very limited, their common feature is the lack of overlap in significant results both, between and even within the studies. Similarly, to our study, Wu et al [9] applied the same GWAS model to feet and leg disorders in three breeds and depending on breed identified different significant regions between Danish Red and Danish Holstein, while no significance was observed in Jersey. In addition, earlier van der Spek et al [10] found a very low overlap in significance while analysing a cow data set and a bull data set ascertained from the same population of Holstein-Friesian cattle, with only three SNPs in bulls overlapped with 94 SNPs significant for claw disorders in cows.…”
Section: Discussionsupporting
confidence: 83%
“…The average reliabilities of the de-regressed proofs for milk, fat, and protein yields and mastitis resistance were 0.95, 0.95, 0.95, and 0.85, respectively, in HOL; 0.95, 0.95, 0.95, and 0.83, respectively, in RDC; and 0.92, 0.92, 0.92, and 0.76, respectively, in JER. The details of the imputation from 50 K and High-Density (HD, 700 K) genotypes of these cattle to whole-genome sequence data have been described previously54. Briefly, a multi-breed reference of 3,383 individuals (1,222 HOL, 1,326 RDC, and 835 JER) with HD genotypes was used to impute individuals with 50 K genotypes to the HD level.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, a multi-breed reference of 3,383 individuals (1,222 HOL, 1,326 RDC, and 835 JER) with HD genotypes was used to impute individuals with 50 K genotypes to the HD level. Individuals with the imputed HD genotypes were then imputed to the whole-sequence level using a multi-breed reference of 1,222 individuals from run4 of the 1,000 Bull Genome project (288 HOL, 56 RDC, 61 JER and 743 individuals from different breeds)55 and private sequence data from Aarhus University (23 HOL, 30 RDC and 27 JER)54. IMPUTE2 v2.3.156 was applied to impute 50 K to the HD level, and Minimac257 was used to impute HD to the whole-sequence level.…”
Section: Methodsmentioning
confidence: 99%
“…Imputation from Illumina BovineSNP50 BeadChip (50 K) to Illumina BovineHD BeadChip (high-density, HD) genotypes for these individuals and further to whole-genome sequence variants was described previously [36, 37]. Briefly, genotypes from the 50 K SNP chip for each individual were first imputed to HD genotypes using a multi-breed reference of 3383 animals (1222 HOL, 1326 Nordic Red, and 835 JER).…”
Section: Methodsmentioning
confidence: 99%
“…The accuracy of imputation was above 0.85 for the across-breed imputation of 19,498,365 SNPs. Detailed information about imputation accuracy was previously reported in [37]. For each breed, SNPs with a large deviation from Hardy–Weinberg proportions ( P  < 10 −6 ) or with minor allele frequency (MAF) <0.01 were further excluded.…”
Section: Methodsmentioning
confidence: 99%